FRI0544 EFFICACY AND SAFETY OF CANAKINUMAB IN SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS –EXPERIENCE USING DATA OF THE BIKER REGISTRY. (June 2019) - Horneff, Gerd; Lilienthal, Eggert; Trauzeddel, Ralf; Hospach, Toni; Kallinich, Tilmann; Dressler, Frank; Sailer-Hoeck, Michaela; Ganser, Gerd; Weller-Heinemann, Frank; Heubner, Georg; Urban, Andreas; Rühlmann, Michael; et al.
Abstract : Background: Canakinumab is approved for the treatment of systemic juvenile idiopathic arthritis (sJIA) older than 2 years. Objectives: The aim of the German Biologics Registry (BiKeR) is the surveillance of JIA patients exposed to biologics. Methods: Baseline demographics and disease activity parameters were documented. Efficacy was determined using the JADAS and the proposed criteria for inactive disease on medication. Safety assessments were based on reports of adverse events (AE). All reports have been coded according to MedDRA ®. Results: 48 sJIA patients with 82.5 patient-years (PY) of exposure to Canakinumab were recorded in the German BiKeR registry. The total observation time (from date of first dose until last follow-up, censored, if another biologic was started) was calculated with 109.9 PY. The cohort treated with Canakinumab had experienced long disease duration of 2.9+/-3.8 years (mean +/- SD). 21 (44%) were pre-treated with methotrexate, 10 (21%) with Etanercept, 3 (6%) with Adalimumab, 18 (38%) with Anakinra and 19 (40%) with Tocilizumab. Concomitantly, 9 (18.8%) received methotrexate, 22 (45.8%) NSAIDs and 23 (48%) systemic corticosteroids. At last follow up upon treatment, 48%/44%/42%/38% of patients reached PedACR30/50/70/90 improvement. 8 patients (16.7%) had inactive disease according to the Wallace criteria. The median (IQR1-IQR3) JADAS10 score decreased from 12.6 (6.2-15.8) at baseline to 0.5 (0.0-2.8). During ongoing treatment, approximately 82% of patients achieved a JADAS defined minimal disease activity; while 64% reached a JADAS defined remission at last follow-up. 125 adverse events (AE) were recorded (114 events/100PY [95% CI 96-136]). Of these, 22 qualified as serious adverse events (SAE) (20/100PY [13-30]). 100 AEs were observed during exposure or up to 90 days follow up after the last exposure to Canakinumab (121/100PY [99-147]). 19 qualified as SAE (23/100PY [15-36]). Adverse Events of Special Interest were serious and medically important infection (n=4), cytopenia (n=4), macrophage activation syndrome (n=3). There was no opportunistic infection, intestinal perforation, anaphylaxis or other hypersensitivity, thrombotic event, evolving autoimmune disease, cardiac or cerebral event, bleeding, malignancy, or death. A total of 38 patients (79%) discontinued treatment, 8 (17%) due to lack or efficacy, 16 (33%) due to remission and 2 (4%) because of intolerance. Conclusion: The current analysis adds to the established safety profile of Canakinumab and demonstrates that safety was comparable and consistent with the overall AE profile of Canakinumab in paediatric patients. MAS occurred in three sJIA patients and might be a JIA-associated feature. Infections were the most frequent AE, but only two serious infections were reported. No new safety signals specific to the paediatric population were identified for Canakinumab; the risk profile of Canakinumab remains positive for the approved paediatric indication sJIA. References: [1] Horneff G, Klein A, Klotsche J, Minden K, Huppertz HI, Weller-Heinemann F, Kuemmerle-Deschner J, Haas JP, Hospach A. Comparison of treatment response, remission rate and drug adherence in polyarticular juvenile idiopathic arthritis patients treated with etanercept, adalimumab or tocilizumab. Arthritis Res Ther. 2016Nov24;18(1):272 Acknowledgement: The authors acknowledge all contributors to BIKER, patients, parents and study staff Disclosure of Interests: Gerd Horneff: None declared, Eggert Lilienthal: None declared, Ralf Trauzeddel: None declared, Toni Hospach Speakers bureau: Chugai, Roche, Novartis, Tilmann Kallinich Grant/research support from: Novartis, Speakers bureau: Sobi, Roche, Novartis, CLB, Frank Dressler Paid instructor for: Abbvie, Pfizer, Novartis, Michaela Sailer-Hoeck: None declared, Gerd Ganser: None declared, Frank Weller-Heinemann: None declared, Georg Heubner: None declared, Andreas Urban: None declared, Michael Rühlmann: None declared, Christoph Rietschel: None declared, Markus Hufnagel: None declared, Wolfgang Emminger: None declared, Ariane Klein: None declared